2012
DOI: 10.1371/journal.pone.0031678
|View full text |Cite
|
Sign up to set email alerts
|

Kosmotropic Anions Promote Conversion of Recombinant Prion Protein into a PrPSc-Like Misfolded Form

Abstract: Prions are self-propagating proteins involved in transmissible spongiform encephalopaties in mammals. An aberrant conformation with amyloid-like features of a cell surface protein, termed prion protein (PrP), is thought to be the essential component of the infectious particle, though accessory co-factor molecules such as lipids and nucleotides may be involved. The cellular co-factors and environmental conditions implicated in PrP misfolding are not completely understood. To address this issue, several studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 61 publications
4
18
0
Order By: Relevance
“…Specifically, strongly hydrated anions (kosmotropes) initiate nucleation quickly and promote rapid fiber elongation, whereas poorly hydrated anions (chaotropes) delay nucleation and mildly affect the elongation rate (43,44). A similar effect of kosmotropes has also been observed by another group for the mammalian prion protein PrP (45). Moreover, amyloid formation by Sup35NM in the presence of different anions resulted in the generation of different spectra of prion strains, with kosmotropes favoring the formation of strong strains (characterized by smaller aggregate size and higher efficiency of fragmentation and proliferation), and chaotropes favoring the formation of weak strains (characterized by larger aggregate size and lower efficiency of fragmentation and proliferation) (43,44).…”
supporting
confidence: 57%
“…Specifically, strongly hydrated anions (kosmotropes) initiate nucleation quickly and promote rapid fiber elongation, whereas poorly hydrated anions (chaotropes) delay nucleation and mildly affect the elongation rate (43,44). A similar effect of kosmotropes has also been observed by another group for the mammalian prion protein PrP (45). Moreover, amyloid formation by Sup35NM in the presence of different anions resulted in the generation of different spectra of prion strains, with kosmotropes favoring the formation of strong strains (characterized by smaller aggregate size and higher efficiency of fragmentation and proliferation), and chaotropes favoring the formation of weak strains (characterized by larger aggregate size and lower efficiency of fragmentation and proliferation) (43,44).…”
supporting
confidence: 57%
“…Similar to temperature, the ionic composition of the solution has been shown to affect aggregation kinetics in a number of amyloid-forming proteins, including ␣-synuclein (41), mouse prion protein PrP (42,43), PABPN1 (44), and Sup35NM (18); however, the effect of solution composition on amyloid structures and biological effects was not studied in detail. The present work relates the differences in aggregation kinetics of Sup35NM caused by different salts to the structures and propagation parameters of amyloids formed in respective conditions.…”
mentioning
confidence: 99%
“…Interestingly, calcium is known to be a highly destabilizing cation within the series, whereas in addition being an activator of PK activity (24). We previously found that NaF efficiently promoted the conversion of recPrP to a PrP Sc -like state, probably by salting-out effects (20). Although the concentrations used in that work were higher than those reported here, a similar saltbased stabilization mechanism may be operating with PrP Sc , and additional experiments are ongoing to explore this scenario.…”
Section: Discussionmentioning
confidence: 67%
“…In particular, the concentrations of sodium chloride and several metals can greatly change PrP Sc sensitivity to proteolysis (19). Kosmotropic salts and copper can also induce misfolding of recombinant PrP into PrP Sc -like species in vitro (20).…”
Section: In Vitro Replication Of Mammalian Infectious Prions Was Firsmentioning
confidence: 99%